2017
DOI: 10.1002/ijgo.12399
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the utility of a point‐of‐care glucometer for the diagnosis of gestational diabetes

Abstract: Use of the Roche Accuchek Active glucometer for the diagnosis of GDM cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 26 publications
3
15
0
Order By: Relevance
“…Importantly, 87.8% of GDM-positive diagnoses in this study population were based on an elevated FPG. This confirms the RESEARCH findings of Macauley et al [3] and Adam and Rheeder [24] that the majority of GDM diagnoses in SA women screened were based on an elevated FPG. The use of FPG alone to screen for GDM is attractive as it is less expensive than a complete OGTT, avoids the need for multiple punctures, reduces laboratory workload, and avoids exposing pregnant women to the sometimes emesis-inducing oral glucose load.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Importantly, 87.8% of GDM-positive diagnoses in this study population were based on an elevated FPG. This confirms the RESEARCH findings of Macauley et al [3] and Adam and Rheeder [24] that the majority of GDM diagnoses in SA women screened were based on an elevated FPG. The use of FPG alone to screen for GDM is attractive as it is less expensive than a complete OGTT, avoids the need for multiple punctures, reduces laboratory workload, and avoids exposing pregnant women to the sometimes emesis-inducing oral glucose load.…”
Section: Discussionsupporting
confidence: 88%
“…Macauley et al [3] reported a 9.1% GDM prevalence in a tertiary hospital setting, using a research laboratory (glucose oxidase method), and their participants had a higher risk profile for GDM than participants at the CHC where this study was conducted. [3] A study by Adam and Rheeder [24] possibly overestimated the GDM prevalence at 25.8%, and one reason for this is that the laboratory bias of 3.65%, which is not within the ≤2.2% recommended by the NACB, [20] would adversely affect the quality of plasma glucose measures. Importantly, 87.8% of GDM-positive diagnoses in this study population were based on an elevated FPG.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with gold standard laboratory glucose determination for the diagnosis of GDM, POCT revealed discordant results in other South Africa studies. Adam and Rheeder [16], concluded that the POCT device, cannot be recommended because the diagnostic sensitivity of POCT compared with the laboratory method was poor (26%). However, in another South Africa study that utilized the same device, good correlations between the POCT and laboratory values were documented in women with GDM, but that study had limited patient numbers [29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in South Africa have examined the ability of POCT to diagnose GDM, with conflicting results [15,16], but confounders that may influence glucose evaluation during gestation are absent in the post-partum period. Previous studies in South Africa have examined the ability of POCT to diagnose GDM, with conflicting results [15,16], but confounders that may influence glucose evaluation during gestation are absent in the post-partum period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation